The anticipatory stress response to sport competition; a systematic review with meta-analysis of cortisol reactivity. Issue 1 (17th September 2017) - van Paridon, Kjell N; Timmis, Matthew A; Nevison, Charlotte M; Bristow, Matt
Abstract : Objective: Athletes anticipating sport competition regularly experience distinct emotional and physiological responses as a result of the expected psychosocial and physical stress. Specifically, cortisol, an indicator of hypothalamic-pituitary-adrenal axis activation, prepares the athlete for the psychological and physiological demands of competition. The objective of this meta-analysis is to analyse the magnitude of the anticipatory cortisol response in athletes preparing to participate in sport competition and to examine the influence of gender, level of competition and data collection time. Design: Systematic review with meta-analysis. Data sources: Four electronic databases were searched to March 2017: PubMed, PsycINFO, SPORTDiscus and Scopus. Eligibility criteria for selecting studies: (1) Athletes participating in real sport competition;(2) salivary cortisol concentration collected before competition in addition to baseline sample(s);(3) original research article published in English language. Results: Data from 25 studies provided 27 effect sizes. A significant anticipatory cortisol response of g=0.85, p<0.001 was identified. Males had a stronger trend for greater cortisol reactivity (g=1.07) than females (g=0.56, p=0.07). Females and athletes competing at international level did not demonstrate a significant anticipatory stress response. There were no significant differences between level of competition, type of sport or time of competition. Meta-regression indicated that the anticipatory cortisol response is greater when assessed closer to the start of competition (Q=6.85, p=0.009). Summary/conclusion: The anticipatory cortisol response before sport competition reflects moderate cortisol reactivity that prepares athletes optimally for the demands of sport competition via the influence on cognitive processes and attentional control. However, both female athletes and international competitors did not demonstrate a significant anticipatory cortisol response, possibly due to differences in appraisal of the stress of sport competition.